Developing Students’ Vocabulary Mastery through the Use of Text Twist Game - Putri Andini; Rofiqoh Rofiqoh; Maf'ulah Maf'ulah; Nur Sehang Thamrin (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This study aims to examine whether the use of the Text Twist Game can improve the vocabulary mastery of seventh-grade students at SMP Negeri 15 Palu. A quasi-experimental research design was employed involving two groups: an experimental group and a control group. The study used quantitative research with purposive sampling. Class VII A with 30 students was the experimental group, and Class VII B with 30 students was the control group. A vocabulary test was used as the instrument for data collection, administered both before (pre-test) and after (post-test) the treatment. The experimental group received instruction using a Text Twist Game, while the control group was taught using an explanation technique. The findings show that the post-test mean score of the experimental group is 56.33 while the control group’s post test mean score is 30. Additionally, the statistical analysis revealed that the value of the t-counted is greater (97.20) than the value of the t-table (0.117). It indicates that the vocabulary mastery of the experimental group outperformed that of the control group after getting treatment. In other words, the use of Text Twist Game is effective to improve students’ vocabulary mastery.